Impact of Institutional Quality and Governance on Financial Inclusion for Women in South Africa: A Case of Gauteng Women Entrepreneurs (The Strategic Review for Southern Africa, 2021)
This paper describes a study of South Africans’ national perception and alignment to financial inclusion for women. It explains the impact of institutional roles and governance on financial inclusion in South Africa. There is ample evidence of government eff orts on implementing fi nancial inclusion in the country. Still, the significance of how governance and institutions promote access to finance for women has been overlooked in the literature. The main objective of this study is to identify the impact of institutional quality and governance on financial inclusion for women in South Africa. Data for analytical purposes supporting the research has been obtained from primary sources through semi-structured open-ended interviews collected from 2019 to 2020. The research approach employed and coded data from a recent study on 30 women entrepreneurs, five key policymakers on women empowerment and fi ve fi nancial institutions supervisors on financial inclusion for women. The results obtained suggest that there is little institutional quality and governance on financial inclusion for women, and further eff orts must be intensifi ed to achieve equal access to financial services in South Africa. Furthermore, the paper presents recommendations for policymakers that, if implemented, would prove fruitful. Policymakers are expected to facilitate gender-mainstreaming/strategies and working policies, monitoring and evaluation, financial literacy, and transparent legal framework on financial policies addressing women.